2019
DOI: 10.3389/fpls.2019.01421
|View full text |Cite
|
Sign up to set email alerts
|

Green Fluorescent Protein- and Discosoma sp. Red Fluorescent Protein-Tagged Organelle Marker Lines for Protein Subcellular Localization in Rice

Abstract: The subcellular localization of proteins is a fundamental aspect of protein functions. Determining the subcellular localization is important for understanding the biological functions of proteins. Here, we developed a set of rice organelle marker lines, in which the expressing fluorescent organelle markers could be used as comparative standards in determining the subcellular localization of the protein of interest. We constructed green fluorescent protein (GFP)- and/or Discosoma sp. red fluorescent protein (Ds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…To analyze the subcellular localization of CiMADS43 , the 35S::CiMADS43-GFP (Green fluorescent protein) fusion vector and 35S::GFP empty vector (control) were transiently expressed in epidermal cells of tobacco leaves. Red fluorescent protein (RFP) labeled was used as a nuclear marker to indicate the location of the nucleus [ 55 ]. The green fluorescence of the CiMADS43-GFP fusion proteins was observed in the nucleus, whereas the signals of the control were distributed on the whole cell ( Figure 1 c).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the subcellular localization of CiMADS43 , the 35S::CiMADS43-GFP (Green fluorescent protein) fusion vector and 35S::GFP empty vector (control) were transiently expressed in epidermal cells of tobacco leaves. Red fluorescent protein (RFP) labeled was used as a nuclear marker to indicate the location of the nucleus [ 55 ]. The green fluorescence of the CiMADS43-GFP fusion proteins was observed in the nucleus, whereas the signals of the control were distributed on the whole cell ( Figure 1 c).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the subcellular localization of OsMBD707, we performed transient expression of a GFP-OsMBD707 fusion construct in rice protoplasts. Microscopy revealed that the fluorescence signal of GFP-OsMBD707 was inside the nucleus region, which was merged with the signal of the nucleus DsRed-OsH2B marker [ 29 ] (Fig. 3 b).…”
Section: Resultsmentioning
confidence: 99%
“…Rice protoplasts were prepared from the sheath and stem tissues of 2-week-old etiolated seedlings. The GFP alone and GFP-OsMBD707 fusion constructs were, respectively, co-transfected with a nucleus marker construct DsRed-OsH2B [ 29 ] into rice protoplasts via a PEG-mediated method as previously described [ 55 ]. Rice stable transformation was conducted as previously described [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The full-length ZmSRL5 coding sequence without the termination codon was obtained by PCR using the PEGAD-SRL5-F/R primers (Table S1), which was inserted into the PEGAD-GFP vector to generate a ZmSRL5 -GFP fusion protein. RFP-OsPIP2 was used as plasma membrane marker (Chen et al 2019). The fusion construct was introduced into the tobacco leaf epidermis, and an Olympus FluoView™ FV1200 confocal microscope (Olympus, Tokyo, Japan) was used to detect the GFP and RFP (red plasma membrane marker) signals.…”
Section: Subcellular Localization Of Zmsrl5mentioning
confidence: 99%